2022
DOI: 10.1002/nop2.1428
|View full text |Cite
|
Sign up to set email alerts
|

The maternal employment status after the completion of their child's cancer treatment: A cross‐sectional exploratory study

Abstract: Aim To clarify the details of mothers' employment status after the completion of their child's cancer treatment. Design A cross‐sectional exploratory study. Methods Data are collected from 62 mothers of childhood cancer survivors using self‐report questionnaires. Fisher's exact test was used to determine the statistical significance of factors between the mothers who worked and those who did not work after their child's cancer treatment had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…If a mother is highly anxious about the physical and mental health of her CCS, including recurrence, then their motivation to work is considered to be low. Meanwhile, similar to previous studies [22], more than 60% of the nonworking mothers in the present study showed motivation to work. In a survey of Japanese working parents with children aged 0-6 years [31], 75.3% of mothers reported difficulty in balancing work and childcare, with the biggest reason being that they had to work with time in mind.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…If a mother is highly anxious about the physical and mental health of her CCS, including recurrence, then their motivation to work is considered to be low. Meanwhile, similar to previous studies [22], more than 60% of the nonworking mothers in the present study showed motivation to work. In a survey of Japanese working parents with children aged 0-6 years [31], 75.3% of mothers reported difficulty in balancing work and childcare, with the biggest reason being that they had to work with time in mind.…”
Section: Discussionsupporting
confidence: 92%
“…We developed a questionnaire based on previous studies [ 11 , 14 , 22 , 23 ], and experts in pediatric oncology examined its validity. For the care demands question items, we listed care that was predicted to affect mothers’ employment referring to research on the employment of mothers of children with disabilities [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although financial hardship is common among long‐term survivors of childhood cancer, 6,23–25,38 these findings of higher odds of hardship among adult siblings versus the general adult population add to accumulating research examining the economic effects of a cancer diagnosis on family members. Several studies have reported declines in parental income and employment during treatment and survivorship 17,18,39,40 . Additionally, families typically experience increases in non–health care out‐of‐pocket spending that exceed what is reported among adults with cancer 21,22 and report increased rates of material hardship after starting therapy that concerningly continue after treatment is complete 41,42 .…”
Section: Discussionmentioning
confidence: 99%